Numerical analysis of concrete-filled double skin tubular slender columns with internal circular and external hexagonal tubes - Morteza Naghipour (Iranian Society of Structrual Engineering (ISSE), 2021)
ABSTRACTA new kind of double skin CFT has more benefits in construction of bridge and especial buildings due to easily multi beam connections for central columns. In this study 27 double skin specimens filled with concrete, consist of internal circular tube and external hexagonal tubes have been studied using ABAQUSE finite element software. The effects of some parameters on behavior of CFT consists of: height of column, width to thickness ratio of external steel tube, diameter to thickness of internal tube and eccentricity were considered. Loading was applied as an axially compression in a displacement control state. The results show that whenever the eccentricity is matched through gap of two skins, the concrete confinement does not reduce, which is not the same as some codes of practice recommendations. The increase on strength of column depends on height, eccentricity and width to thickness ratio of external tube. The strength reduction of columns is up to 15% when height increases 50%. When the diameter to thickness, eccentricity and height of specimens remain constant, it was considered through the results that, the effects of width to thickness ratio of models is more significant than other parameters. The results also show that, when the height is constant and the width to thickness of external tube increases some outward foldings on columns were existed.